Cosmological constraints from higher redshift gamma-ray burst, H ii starburst galaxy, and quasar (and other) data. Issue 1 (3rd December 2020) - Cao, Shulei; Ryan, Joseph; Khadka, Narayan; Ratra, Bharat
ABSTRACT: We use higher redshift gamma-ray burst (GRB), H ii starburst galaxy (H ii G), and quasar angular size (QSO-AS) measurements to constrain six spatially flat and non-flat cosmological models. These three sets of cosmological constraints are mutually consistent. Cosmological constraints from a joint analysis of these data sets are largely consistent with currently accelerating cosmological expansion and with cosmological constraints derived from a combined analysis of Hubble parameter ( H ( z )) and baryon acoustic oscillation (BAO, with Planck -determined baryonic matter density) measurements. A joint analysis of the H ( z ) + BAO + QSO-AS + H ii G + GRB data provides fairly model-independent determinations of the non-relativistic matter density parameter $Ω _{\rm m_0}=0.313± 0.013$ and the Hubble constant $H_0=69.3± 1.2\, \rm {km \, s^{-1} \, Mpc^{-1}}$ . These data are consistent with the dark energy being a cosmological constant and with spatial hypersurfaces being flat, but they do not rule out mild dark energy dynamics or a little spatial curvature. We also investigate the effect of including quasar flux measurements in the mix and find no novel conclusions.